Clozapine‐associated severe eosinophilia following lithium rebound neutropenia: A case report - Kota Kikuchi; Norio Yasui‐Furukori; Saaya Yokoyama; Chie Hasegawa; Atsuhiko Kokubun; Shinichi Katsukura; Taro Shimizu; Kazutaka Shimoda (Wiley, 2020)
Abstract Background Clozapine use is complicated by an increased risk of hematological adverse effects such as neutropenia and, rarely, eosinophilia. Case presentation We present the case of a 48‐year‐old man with treatment‐resistant schizophrenia. On day 12 after clozapine initiation, he had a cough with a temperature of 39.8°C. On day 16, his leukocyte count had increased to 9320 cells/mm3 (neutrophils 7550 cells/mm3 and eosinophils 680 cells/mm3). We discontinued lithium because of neutrophilia and damage to renal function on day 20. His eosinophil count increased until day 29, reaching 6750 cells/mm3. We suspected a drug‐induced reaction and discontinued clozapine on day 30. His eosinophil count gradually decreased, reaching the normal range by day 40. However, his leukocyte and neutrophil counts also gradually decreased to below than the normal range by day 40. His leukocytes and neutrophil counts had recovered by day 55. Conclusion We concluded that this patient had clozapine‐associated severe eosinophilia following lithium rebound neutropenia.